High temperature noble gas thermometry in Lake Kivu, East Africa - Schwenk, Cornelis; Negele, Sophie; Balagizi, Charles M.; Aeschbach, Werner; Boehrer, Bertram (The science of the total environment, 2022)
Due to their biological and chemical inertness, noble gases in natural waters are widely used to trace natural waters and to determine ambient temperature conditions during the last intensive contact with the atmosphere (equilibration). Noble gas solubilities are strong functions of temperature, with higher temperatures resulting in lower concentrations. Thus far, only common environmental conditions have been considered, and hence investigated temperatures have almost never exceeded 35 °C, but environmental scenarios that generate higher surface-water temperatures (such as volcanism) exist nonetheless. Recently published measurements of noble gas concentrations in Lake Kivu, which sits at the base of the Nyiragongo volcano in East Africa, unexpectedly show that the deep waters are strongly depleted in noble gases with respect to in-situ conditions, and so far no quantitative explanation for this observation has been provided. We make use of recently published noble gas solubility data at higher temperatures to investigate our hypothesis that unusually high equilibration temperatures could have caused the low measured noble gas concentrations by applying various approaches of noble gas thermometry. Noble gas concentration ratios and least squares fitting of individual concentrations indicate that the data agrees best with the assumption that deep water originates from groundwater formed at temperatures of about 65 °C. Thus, no form of degassing is required to explain the observed noble gas depletion: the deep water currently contained in Lake Kivu has most probably never experienced a large scale degassing event. This conclusion is important as limnic eruptions were feared to threaten the lives of the local population.